Eugenol hydrodeoxygenation employing bifunctional Ni-Pd and Ni-Pt catalysts on zirconium pillared clays - Zamora-Rodea, Emigdio Gregorio (2023)
This work evaluated bifunctional mono and bimetallic catalysts of Ni, Pd, and Pt using total metallic loading lesser than 3% wt. percent supported on pillared clays modified with zirconium cations in the hydrodeoxygenation reaction of eugenol at medium pressure conditions and temperature, 3 MPa, and 573 K, respectively. The catalysts were texturally and structurally characterized by means of N2 physisorption and X-ray diffraction. The impregnation of the metallic phases was carried out through the solid-state impregnation method. The monometallic catalyst that presented the highest activity was that of Pd, k= 4.94 x10-2 min-1; a conversion of 99.98% was reached at 75 min of reaction and selectivities to 4-propylphenol and propyl-cyclohexane, 22 and 29 % molar, respectively. In the case of bimetallic catalysts, the most active was 1Ni1Pd, k= 3.83 x10-2 min-1, reaching a conversion of 99.6% at 105 min and selectivities to 4-propylphenol and propyl-cyclohexane, 14 and 31% molar, respectively; derivated of demethoxylation and hydrodeoxygenation reactions. Furthermore, it was found that the H/C molar ratio using the 1Pt catalyst was equal to 1.93, close to that found in commercial jet fuels (1.98) or even higher than that of aviation biofuels reported in the literature (1.37).